Korpora in Der Germanistischen Sprachwissenschaft 2023
DOI: 10.1515/9783111085708-005
|View full text |Cite
|
Sign up to set email alerts
|

Das Forschungs- und Lehrkorpus für Gesprochenes Deutsch (FOLK)

Abstract: Der Beitrag illustriert die Nutzung des Forschungs-und Lehrkorpus Gesprochenes Deutsch (FOLK) für interaktionslinguistische Fragestellungen anhand einer exemplarischen Studie. Zunächst werden die Stratifikation (Datenkomposition) des Korpus, das zugrundeliegende Datenmodell und dessen Annotationsebenen sowie Typen von Untersuchungsinteressen vorgestellt, für die das Korpus nutzbar ist. Im Hauptteil wird Schritt für Schritt anhand einer Studie zur Verwendung des Formats was heißt X in der sozialen Interaktion g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…3 Günthner (2015) mentions differences between the two uses of Was heißt X concerning delay of turn-production, position of focal accent, and intonation. 4 The study reported here is based on 119 instances of Was heißt X from videorecordings and telephone conversations from the public corpus FOLK version 2.18 (2022) (accessible via https://dgd.ids-mannheim.de; Reineke et al 2023). 5 All data extracts were submitted to close sequential analysis according to the principles of CA (Robinson et al 2024) and IL (Couper-Kuhlen & Selting 2018).…”
Section: Uses Of and Responses To Was Heißt X ('What Does X Mean') In...mentioning
confidence: 99%
“…3 Günthner (2015) mentions differences between the two uses of Was heißt X concerning delay of turn-production, position of focal accent, and intonation. 4 The study reported here is based on 119 instances of Was heißt X from videorecordings and telephone conversations from the public corpus FOLK version 2.18 (2022) (accessible via https://dgd.ids-mannheim.de; Reineke et al 2023). 5 All data extracts were submitted to close sequential analysis according to the principles of CA (Robinson et al 2024) and IL (Couper-Kuhlen & Selting 2018).…”
Section: Uses Of and Responses To Was Heißt X ('What Does X Mean') In...mentioning
confidence: 99%